KEADAAN SARANA DAN PRASARANA PEMBELAJARAN PENDIDIKAN JASMANI DI SEKOLAH MENENGAH PERTAMA NEGERI SE-KECAMATAN KENDAL - Minan Zhein, Muhammad Ahsanul; Septianingrum, Kartika; Prayoga, Aba Sandi (Dharmas Journal of Sport, 2024)
Based on initial findings, information about the condition of facilities and infrastructure that support Physical Education learning in Junior High Schools in Kendal District, Ngawi Regency is needed. This quantitative descriptive research aims to determine the results of a description of the state of Physical Education learning facilities and infrastructure in Junior High Schools in Kendal District, Ngawi Regency. This research uses a survey method to find out the results. The questionnaire is used to determine the existence and condition of infrastructure and facilities. The Junior High School in Kendal District, Ngawi Regency, which consists of three schools, was used as the subject of this research. Quantitative descriptive analysis is used by classifying the types of data obtained from observation sheets and combining them into groups. According to the research results, there are 2 junior high schools in Kendal District, Ngawi Regency which have physical education facilities and infrastructure in the medium category, which means 66.7% of the 33% total or one school is in the good category.